Digital Marketing Training through Copywriting Techniques And SEO for Social Forestry Business Groups Bungo Residential Office - Istianingsih, Nanik; Muhammad, Ariyanto; Zulkifli, Zulkifli; Juniarsih, Delvita; Rianto, Rianto (Society : Jurnal Pengabdian Masyarakat, 2025)
In today's technological era, digital marketing is one of the keys to running a successful business. Digital marketing implementation includes scriptwriting techniques and search engine optimization (SEO). Through the implementation of this activity, forestry business groups will be trained to know, understand, and apply information technology for digital marketing activities. Based on initial interviews with the management partners of the business group, several key issues in marketing their business were identified. First, digital marketing insights; second, techniques to increase online sales; third, improving product reputation; and fourth, improving product quality, packaging, and presentation. The training will explain digital marketing and teach two digital marketing techniques: copywriting and SEO, depending on the needs of the participants. The stages of implementing this community service are, first, learning digital marketing skills, second, understanding copywriting, and third, practicing the application of SEO to the participants' businesses. The training includes lectures, exercises, discussions and practical exercises. The results of the activity will be evaluated through a question and answer session with participants. From the results of this activity, it is hoped that the participants of the business group will start applying search engine optimization techniques in running their businesses.